Analisis Pemberian Kredit terhadap Pendapatan Bunga Bersih Pada PT Bank DKI - Yohana Marsaulina Manurung; Sofyan Marwansyah (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2017)
Credit is a bank product that provides greater benefits than other bank products. The amount of credit granted by the bank affects the income level earned in a period, one of which is net interest income. The purpose of this research is to know the relationship between crediting and net interest income of PT Bank DKI. The author uses quantitative analysis by using the correlation coefficient test method, test coefficient of determination, and test the regression equation processed using SPSS software. The data of credit disbursement and net interest income obtained from Annual Report in the form of balance sheet and income statement of PT Bank DKI for the period of 2005-2015. By doing the analysis, it can be seen the correlation relationship between the provision of credit and net interest income is significant because the value of Sig. Of 0.000 <0.05 and has a strong and unidirectional relationship to net interest income because the value of correlation coefficient formed at 0.980. The effect of lending and net interest income is significant because the value of Sig. Amounted to 0,000 <0.05 and net interest income was influenced by the lending of 96.1% and the remaining 3.9% influenced by other factors. And the regression equation that formed between giving credit to net interest income is significant because the value of Sig. Of 0.000 <0.05.